The Effect of Human Resource Planning, Quality of Work Life, and Motivation on Employee Job Satisfaction among Cashiers at PT XYZ, Yogyakarta Branch, Bantul Regency - mei rahmawati (Prodi Manajemen, 2025)
This study investigates the effect of Human Resource Planning, Quality of Work Life, and Motivation on Employee Job Satisfaction among cashiers at PT XYZ, Yogyakarta Branch, Bantul Regency. Employing a quantitative survey approach, data were collected from 67 respondents using structured questionnaires. The analysis was conducted using descriptive statistics, validity and reliability testing, and multiple linear regression via SPSS version 28. The results indicate that, individually, Human Resource Planning, Quality of Work Life, and Motivation have a significant positive effect on Employee Job Satisfaction, with t-values of 10.652, 8.652, and 7.073, and significance levels below 0.05. Simultaneously, the three variables collectively exert a significant influence on Employee Job Satisfaction (F = 216.748, p < 0.05). The adjusted R² of 0.895 indicates that 89.5% of the variance in employee job satisfaction is explained by the independent variables. Among them, Human Resource Planning emerges as the most dominant factor. These findings highlight the critical role of strategic HR planning, supportive work-life quality, and employee motivation in enhancing job satisfaction within organizational settings. Keywords: human resource planning, quality of work life, motivation, employee job satisfaction, multiple linear regression